Circular Economy Makan Bergizi Gratis Program: A Conceptual Product Based On Islamic Economy - Arivatu Ni'mati Rahmatika Rahmatika; Bekti Widyaningsih Widyaningsih; Trisna Putri Anggraeni Anggraeni (LP2M IAIN Palopo, 2026)
Makan Bergizi Gratis Program (MBG) is a government policy to improve the quality of human resources by providing healthy food for school children. This program not only focuses on nutritional aspects, but also stimulates the local economy through the application of circular economy principles. This study aims to analyze the application of circular economy in the MBG program and review its relevance from an Islamic economic perspective. The method used is qualitative descriptive-conceptual with a literature study approach sourced from scientific literature, news articles, the Qur'an, hadith, and the thoughts of Islamic figures such as Al-Ghazali and Ibn Khaldun. The analysis was conducted using content analysis techniques to map concepts related to resource circulation, local food supply chains, and Islamic ethical principles. The results show that the MBG program has implemented circular economy principles through budget efficiency, the use of local food ingredients, waste management, and community empowerment. From an Islamic perspective, this program indicates the harmony between the circular economy mechanism of the MBG and the values ​​of social justice, wealth distribution, and public welfare as stated in QS. Al-Hasyr verse 7 and QS. At-Taubah verse 60. Islamic philanthropy such as zakat, infaq, sedekah, and waqf has the potential to support the sustainability of this program and strengthen the people's economy. Thus, the MBG represents a concrete implementation of collaboration between the circular economy and Islamic values ​​to achieve sustainable prosperity.